Adolescent Sugar-Sweetened Beverage Intake is Associated With Parent Intake, Not Knowledge of Health Risks. Issue 8 (November 2018) - Lundeen, Elizabeth A.; Park, Sohyun; Onufrak, Stephen; Cunningham, Solveig; Blanck, Heidi M.
Purpose: To examine associations of adolescent sugar-sweetened beverage (SSB) intake with parent SSB intake and parent and adolescent knowledge of SSB-related health risks. Design: Quantitative, cross-sectional. Setting: 2014 SummerStyles survey. Subjects: Nine hundred and ninety parent and adolescent (12-17 years) pairs. Measures: The outcome was self-reported adolescent intake (0, >0 to <1, or ≥1 time/day) of SSBs (soda, fruit drinks, sports/energy drinks, other SSBs). The exposures were self-reported parent SSB intake (0, >0 to <1, ≥1 to <2, or ≥2 times/day) and parent and adolescent knowledge of SSB-related health risks (weight gain, diabetes, and dental caries). Analysis: Separate multinomial logistic regression models were used to estimate adjusted odds ratios (aORs) for adolescent SSB intake ≥1 time/day (ref: 0 times/day), according to (1) parent SSB intake and (2) parent and (3) adolescent knowledge. Results: About 31% of adolescents consumed SSBs ≥1 time/day, and 43.2% of parents consumed SSBs ≥2 times/day. Adolescent and parent knowledge that SSB intake is related to health conditions ranged from 60.7% to 80.4%: weight gain (75.0% and 80.4%, respectively), diabetes (60.7% and 71.4%, respectively), and dental caries (77.5% and 72.9%, respectively). In adjusted models, adolescent SSB intake ≥1 time/day was associated with parent intake ≥2 times/day (aOR = 3.30; 95% confidence interval = 1.62-6.74) but not with parent or adolescent knowledge of health risks. Conclusion: Parental SSB intake may be an important factor in understanding adolescent behavior; knowledge of SSB-related health conditions alone may not influence adolescent SSB behavior.